AN USEFUL AND SIMPLE METHOD IN DIAGNOSIS OF CARPAL TUNNEL SYNDROME: HAND DIAGRAM - Öznur Öken,; Sema Atalay Çatal,; Esma Ceceli,; Z. Rezan Yorgancıoğlu, (Archives of Rheumatology, 2003)
The most common pathology in patients with upper limb paresthesia is Carpal Tunnel Syndrome (CTS). Most valuable clue for diagnosis is obtained from patient's history. Hand diagram developed by Katz and Stirrat has been used for evaluation of patients with upper limb numbness, pins-needles sensation in some of the hand clinics. We also tested hand diagram on patients who were complaining paresthesia in upper extremities. We concluded that, this diagram is an extremely easy to apply and inexpensive method and, it can be used in hand clinics in addition to other diagnostic tests.